Adsorption of cadmium on clay-organic associations in different pH solutions: The effect of amphoteric organic matter - Wenpo Xu; Chengshuai Liu; Jian-Ming Zhu; Hongling Bu; Hui Tong; Manjia Chen; Decan Tan; Ting Gao; Yizhang Liu (Ecotoxicology and Environmental Safety, 2022)
Clay minerals are important soil components and usually coexist with organic matter, forming mineral-organic associations (MOAs), which control the speciation, mobility, and bioavailability of heavy metals. However, the adsorption mechanism of cadmium (Cd) by MOAs is still unclear, especially for the associations of amphotericorganic matter and clay minerals. In this study, 12-aminododecanoic acid (ALA) and montmorillonite (Mt) were chosen to prepare MOAs via intercalation (Mt-ALA composite) and physical mixing (Mt-ALA mixture). Batch experiments were conducted to investigate the adsorption mechanism of Cd(II) by MOAs under different pH values and initial Cd(II) concentrations. The results showed that the Cd(II) adsorption capacities followed as Mt > Mt-ALA mixture > Mt-ALA composite under acidic conditions, Mt-ALA mixture > Mt > Mt-ALA composite under neutral conditions, and Mt-ALA mixture > Mt-ALA composite > Mt under alkaline conditions, suggesting the adsorption behaviors of Cd(II) by MOAs were primarily constrained by the speciation of ALA and solution pH. Under acidic conditions, cationic HALA+ could intercalate into the interlayer of Mt and occupy the adsorption sites, reducing the adsorption capacity of Cd(II). As pH increased to neutral, HALA+ decreased and changed to a zwitterionic state, which caused ALA to release out from the interlayer of Mt-ALA composite or not easily enter into Mt-ALA mixture and promoted Cd(II) adsorption. Under alkaline conditions, the increase of anion ALA- would cause ALA to be mainly adsorbed on the surface of Mt and chelate with Cd(II), enhancing the adsorption of Cd(II). Further analysis by Fourier transform infrared and X-ray photoelectron spectroscopy indicated that the carboxyl and amino groups of ALA both participated in the adsorption of Cd(II). These findings could extend the knowledge on the mobility and fate of Cd in clay-based soils and be used as a basis for understanding the biogeochemical behavior of Cd in the environment.